Osteoarthritis Hip and Knee Service (OAHKS) in a community health setting compared to the hospital setting: A feasibility study for a new care pathway. (October 2020) - Gibbs, Alison J.; Taylor, Nicholas F.; Hau, Raphael; Barton, Christian; Fong, Chris; Roddy, Leanne; Durant, Kylie J.; deVos, Leanne D.; Wallis, Jason A.
Abstract: Aim: OsteoArthritis Hip and Knee Service (OAHKS) clinics involve assessment and triage by advanced musculoskeletal physiotherapists for patients referred to orthopaedic clinics in public hospitals. This study explored the feasibility of implementing an OAHKS clinic in a community setting. Methods: The domains of feasibility explored in this mixed methods study were acceptability (patient, general practitioner and orthopaedic surgeon), demand (referrals, waiting times) efficacy potential (management decision, conversion-to-surgery rates) and practicality (number and type of discussions between advanced musculoskeletal physiotherapist and doctors, adverse events). Results from a community-based OAHKS were compared with hospital-based OAHKS over a 9-month period in the same metropolitan health region. Results: A total of 91 eligible patients attended an OAHKS clinic (40 community-based, 51 hospital-based). Both the community-based and hospital-based OAHKS had high patient and general practitioner satisfaction, with small differences in favour of community-based OAHKS. Waiting times were significantly shorter in community-based OAHKS for both initial appointment [community-based OAHKS mean 17 days (SD11), hospital-based OAHKS mean 155 days (SD38)] and commencing non-surgical management [community-based OAHKS mean 32 days (SD22), hospital-based OAHKS mean 67 days (SD32)]. Referral rate to orthopaedics was substantially lower from community-based OAHKS (3%) compared with hospital-based OAHKS (33%) [odds ratio 0.05 (95% CI 0.01–0.41)]. There were no adverse events. Conclusion: Community-based OAHKS is feasible, and acceptable to patients and general practitioners, with potential benefits indicated in this study including shorter waiting times for assessment and commencing non-surgical management programs. Highlights: Osteoarthritis Hip and Knee Service (OAHKS) in a community setting is feasible. High levels of satisfaction (acceptability) from patients and doctors with community OAHKS. Onsite, quick access to non-surgical management is a potential bonus of community-based OAHKS. Substantially reduced referral rate to orthopaedics with community based OAHKS. Quick access to OAHKS in community setting a further potential benefit.